Improving the use of antibiotics in primary health centres through a problem-based pharmacotherapy training approach - Iwan Dwiprahasto, Iwan Dwiprahasto (Universitas Gadjah Mada, 2003)
Background: Inappropriate use of antibiotics in the treatment of common diseases such as acute respiratory infection (ARI) and diarrhoea has been the major health problems in primary health centres (PHCs). Beside increasing the risk of adverse event, excessive use of antibiotics has also led to bacterial resistance worldwide.Objective: To improve the quality of prescribing of Primary Health Centers (PHCs) physicians and paramedics particularly in the treatment of ARI and diarrhoea.Design: Prospective intervention study with control group involving 113 PHCs physicians in both arms. Thirteen districts were randomly selected for study area, in which intervention was carried out in 8 districts while 5 other districts as control group. A systematic problem-based approach of 3 days training were carried out in the intervention group using 3 sets of modules, followed by self monitoring & regular visit & feedback by a Training Team. Evaluation on prescribing was carried out 3 times, i.e at the 6th , 12th, &18th month after intervention.Results: More than 17 thousands and 8600 prescriptions for ARI and diarrhoea were collected during the study. There was a significant reduction in the use of antibiotics for ARI in the intervention group from 92.3 before the study, to 67.4, 52.8 and 39.5%, 6, 12, & 18 month after the study (p0.05). There has been significant antibiotics prescribing shift toward more rational choice in the intervention group 18 months after the study.Conclusions: A systematic problem-based pharmacotherapy training followed by self monitoring & regular visit & feedback significantly improved antibiotic prescribing for ARI and diarrhoea.Key words: antibiotics - prescribing - problem-based pharmacotherapy training - acute respiratory infection - diarrhoea